Asset specificity in sport - How centralized should an efficient production of elite sporting succes be? - Flatau, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Research Problem Sporting success is a product of giftedness and training. Since the first can be assumed to be distributed equally and the latter causes costs it is not surprising that virtually all surveys on collective sporting success identify population size and gross income product (a proxy variable for financial power) as explaining variables. Hence, from an economic perspective, the productivity of the promotion of elite sport becomes the focus of attention. Theory Every production can be organized more or less hierarchically. According to Williamson (1985), the general comparative profitability of markets decline as the asset specificity of the product and therefore the market transaction costs increase. Applying this approach to collective sporting success, the question is whether its in many countries currently quite hierarchical promotion system could be decentralized without a decline in effectiveness but in costs. Our hypothesis is that asset specificity varies strongly across the different sport and that therefore this but also national characteristics ought to be taken into account for the design of an efficiency-optimized promotion system. State of Research For the field of the promotion of talent development, Emrich & Pierdzioch (2011) identified over-centralization with regard to productivity and Flatau & Emrich (2011) could prove the dependency of that lack of efficiency on the sport-related site and physical asset specificity as assumed above. Here, we present analogous analyses for the promotion of short-term sporting success. Method Using a questionnaire survey sample of 1,558 elite athletes, we compare the sporting success of those preparing for competition (i.e., training, medical/scientific services etc.) centralized at Olympic Training Centres with that of those preparing decentralized (in sport clubs etc.) and measure in how far this relation is intervened by asset specificity, the popularity and the degree of commercialization of the respective sport. Other than in preceding analyses we use metric parameters for site as well as for physical asset specificity basing on training site/facility density and cost measurement. Results and Discussion The results confirm the assumption that the comparative efficiency disadvantages of centralized production of sporting success decrease with increasing asset specificity. Hence, a cost-optimized production of sporting success ought to confine costly centralized promotion organizations to sport with high asset specificity.